Acceptance towards COVID-19 vaccine among Qassim populations: A cross-sectional study - Muslet Alharbi; Norh M. Alharbi; Shumukh M. Almutairi; Maha K. Alharbi; Jolan S. Alsaud; Badr Alnssyan; Waleed Al Abdulmonem (Journal of Family Medicine and Primary Care, 2023)
Introduction: The approval of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) vaccines and obtaining herd immunity raise the optimism about seeing the end of this pandemic but vaccine hesitancy or refusal to vaccinate is a major threat to progress toward achieving herd immunity. In this study, we identify baseline knowledge, myths, misconceptions, attitudes, beliefs, and behaviors toward the COVID-19 vaccine. This help to develop new strategies to raise awareness, correct misconceptions and improve acceptance of the COVID-19 vaccine. This study aim is to evaluate the acceptance of COVID-19 vaccine among population in Qassim region of Saudi Arabia. Methods: This cross-sectional study conducted among target people who were more than 11 years old in Qassim Region of Saudi Arabia using the snowball sample study. A self-administered online questionnaire was used that evaluates the knowledge and acceptance of COVID-19 vaccine among this population. Results: The results show that the participants’ high knowledge of COVID-19 translates into good and safe practices, during the COVID-19 pandemic. Public health workers worldwide should concentrate on enlightening and building faith among the unsure and reluctant population regarding security, effectiveness, and adverse effects of the COVID-19 vaccine. Conclusions: The study findings are useful to the policymakers and healthcare professionals who are working on vaccine awareness programs of COVID-19. The findings conclude that the health education interventions should be directed to population of Qassim, Saudi Arabia, at high risk of contracting COVID-19.